ROS and Oxidative Response Systems in Plants Under Biotic and Abiotic Stresses: Revisiting the Crucial Role of Phosphite Triggered Plants Defense Response - Mohammadi, Mohammad Aqa; Cheng, Yan; Aslam, Mohammad; Jakada, Bello Hassan; Wai, Myat Hnin; Ye, Kangzhuo; He, Xiaoxue; Luo, Tiantian; Ye, Li; Dong, Chunxing; Hu, Bin; Priyadarshani, S. V. G. N.; et al. (Frontiers in Microbiology, 2021)
Phosphite (Phi) is a chemical analog of orthophosphate [HPO43−]. It is a systemic pesticide generally known to control the prevalence of oomycetes and soil-borne diseases such as Phytophthora, Pythium, and Plasmopora species. Phi can also control disease symptoms and the spread of pathogenic bacteria, fungi, and nematodes. Phi plays critical roles as a fungicide, pesticide, fertilizer, or biostimulator. Overall, Phi can alleviate the severity of the disease caused by oomycete, fungi, pathogenic bacteria, and nematodes (leave, stem, fruit, tuber, and root) in various plants (vegetables, fruits, crops, root/tuber crops, ornamental plants, and forests). Advance research in molecular, physiological, and biochemical approaches has approved the key role of Phi in enhancing crop growth, quantity, and quality of several plant species. Phi is chemically similar to orthophosphate, and inside the cells, it is likely to get involved in different features of phosphate metabolism in both plants and pathogens. In plants, a range of physiobiochemical alterations are induced by plant pathogen stress, which causes lowered photosynthesis activities, enzymatic activities, increased accumulation of reactive oxygen species (ROS), and modification in a large group of genes. To date, several attempts have been made to study plant-pathogen interactions with the intent to minimize the loss of crop productivity. Phi’s emerging function as a biostimulant in plants has boost plant yield and tolerance against various stress factors. This review discusses Phi-mediated biostimulant effects against biotic and abiotic stresses.